„Takeaway” culture. Cultural Centre in Górna district in virtual space of culture at the time of a pandemic - Dawidowicz, Agata (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The author of the article, head of the local cultural centre in Łódź, presents preliminary conclusions formulated on the basis of first months of work during pandemic and lockdown. Successive phases of remote work and cultural activity online are characterized. Advantages of such forms of activity are described, as well as their disadvantages, which become more visible in the long term. The text is complemented by statements of the employees of this cultural centre, which are focused on three problem areas: emotions, motivations, development and learning for the future.